DEVELOPMENT OF SMART MATHEMATICS MONOPOLY MEDIA IMPROVE MATHEMATICS LEARNING OUTCOMES - Alpian, Yayan; Solahudin Anwar, Aang; Dewi, Shinta (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to determine the use of smart mathematic monopoly learning media able to improve student mathematics learning outcomes. This research uses the Research and Development (R&D) method. Development of smart mathematics monopoly learning media for flat figure material for Mathematics IV fourth grade subjects. The subjects of this study were all grade IV students of SD Negeri Adiarsa Barat II Karawang Barat with a total of 36 students. The results of the validation of the material experts and media experts were 78% with a decent category and the results of the students’ responses were 91%, the student’s post-test score was 81.39 and with the percentage value of 81% of students who got a score of ≥ 75, while the student’s pre-test score was 60.83 with a percentage value of 25% of students who scored ≥ 75. It can be concluded that the learning media monopoly in smart mathematics flat grade material class IV, feasible and can improve mathematics learning outcomes flat grade material class IV SD Negeri Adiarsa Barat II. This research recommends that the school, especially teachers, be able to design and use creative and innovative learning media to increase student participation and improve student learning outcomes.